Beyond Amyloid: Investigating the Role of Tau Oligomers in Alzheimer's Disease Progression in Medan, Indonesia - Sony Sanjaya; Brenda Jaleel; Cindy Susanti; Yi-Fen Huang; Husin Sastranagara; Agnes Mariska (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive decline and memory impairment. While amyloid plaques have been a central focus of AD research, increasing evidence suggests that tau oligomers play a crucial role in disease progression. This study aimed to investigate the relationship between tau oligomers, cognitive function, and disease severity in AD patients in Medan, Indonesia. Methods: An observasional case series study was conducted involving 50 AD patients diagnosed according to the National Institute on Aging-Alzheimer's Association (NIA-AA) criteria. Cerebrospinal fluid (CSF) samples were collected and analyzed for tau oligomers using an enzyme-linked immunosorbent assay (ELISA). Cognitive function was assessed using the Mini-Mental State Examination (MMSE) and the Clinical Dementia Rating (CDR) scale. Correlation analyses were performed to examine the relationship between tau oligomer levels, cognitive performance, and disease severity. Results: The mean tau oligomer level in AD patients was 120.5 ± 35.2 pg/mL. A significant negative correlation was observed between tau oligomer levels and MMSE scores (r = -0.65, p < 0.001), indicating that higher tau oligomer levels were associated with poorer cognitive performance. Furthermore, tau oligomer levels were positively correlated with CDR scores (r = 0.58, p < 0.001), suggesting a link between tau oligomers and disease severity. Conclusion: This study provides evidence for the involvement of tau oligomers in AD progression in the Indonesian population. Elevated CSF tau oligomer levels are associated with cognitive decline and disease severity in AD patients. These findings highlight the potential of tau oligomers as a therapeutic target and emphasize the need for further research to develop effective interventions.